PENGARUH EFIKASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI DENGAN MINAT INVESTASI SEBAGAI VARIABEL INTERVENING (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Abdurachman Saleh Situbondo Angkatan 2018) - Fatimah, Ratna Dwi; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Students are one of the next generation who will build Indonesia in the future. They need to be prepared to build the Indonesian nation, especially in the economic field. To achieve this, it requires the development and character development of the nation's children who are diligent, disciplined, and of course thrifty and careful in their lives. The purpose of this study is to analyze and test the Effect of Financial Efficacy on Investment Decisions of Students of the Faculty of Economics and Business, Abdurachman Saleh University Situbondo with Investment Interest as an Intervening Variable. The population of this study was 172 students of the Faculty of Economics and Business Force 2018. The sample selection technique used is Probability Sampling, which is simple random so as to obtain a sample of 63 students. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that financial efficacy has a significant positive effect on investment interest, financial efficacy has a significant positive effect on investment decisions, investment interest has a significant positive effect on investment decisions, financial efficacy has a significant positive effect on investment decisions through investment interest.